Integration of digital technology in Higher Studies in Nepal: A Literature-based Synthesis - KC , Subash (Dhaulagiri Journal of Contemporary Issues, 2026)
Digital transformation is an important part of higher education in the global context. Although Nepal is able to adopt e-learning technology, many educational institutions continue to experience challenges related to institutional readiness, technological infrastructure, and human capacity. This article employs an integrative literature review to test the factors, including the e-learning movement in Nepalese higher studies. With the help of a research query addressing institutional, technological, and human willingness, the article synthesizes evidence from the latest literature published between 2019 and 2024. The finding shows that these three dimensions are highly integrated, which determines the success of digital transformation. Poor governance, lack of ICT structure, fewer digital competencies, and less institutional support hinder long-term sustainable implementation. This study also concludes that a strong policy framework, funding for digital infrastructure, and producing capable manpower help to form proper digital transformation in Nepal’s higher education system. The result can guide policymakers, university leaders, and researchers to strengthen digital willingness and support long-term education development.